2022
DOI: 10.3389/fimmu.2022.964179
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators profile in patients hospitalized with COVID-19: A comparative study

Abstract: Abnormal inflammatory mediator concentrations during SARS-CoV-2 infection may represent disease severity. We aimed to assess plasma inflammatory mediator concentrations in patients with SARS-CoV-2 in Addis Ababa, Ethiopia. In this study, 260 adults: 126 hospitalized patients with confirmed COVID-19 sorted into severity groups: severe (n=68) and mild or moderate (n=58), and 134 healthy controls were enrolled. We quantified 39 plasma inflammatory mediators using multiplex ELISA. Spearman rank correlation and Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…In terms of soluble FLT‐1, we included 6 studies 13,48,66,68–70 with 190 patients in poor outcome group and 471 patients in good outcome group. The meta‐analysis derived a pooled standard mean difference of 1.93 (0.65, 3.21) ( p = 0.003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of soluble FLT‐1, we included 6 studies 13,48,66,68–70 with 190 patients in poor outcome group and 471 patients in good outcome group. The meta‐analysis derived a pooled standard mean difference of 1.93 (0.65, 3.21) ( p = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…In total, we analysed the results of VEGF serum levels in 466 patients (227 with poor outcome and 239 with good outcome) from 6 studies. 9,45,48,51,66,67 The meta-analysis derived a pooled standard mean difference of 0.27 (0.02, 0.53) (p = 0.03) which indicates increasing levels of VEGF in patients suffering a critical form of COVID-19. The heterogeneity among these studies was moderate (I 2 = 35%, p = 0.17) (Figure 4, panel A).…”
Section: Vegf and Sflt-1mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research, TNF and CCL3 could mediate the inhibition of human intestinal mast cell activation by resveratrol ( 42 ). Additionally, CCL3 and TNF were found to increase in critically ill patients with COVID-19 and related to increased morbidity and mortality ( 43 ). Moreover, the researchers found that FCGR3A is mainly expressed on immune cells (like NK cells) and also correlated with the severity of COVID-19 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 is another biomarker of endothelial perturbation; in particular, it is a glycoprotein expressed at the endothelial cell surface level whose expression is increased by pro-inflammatory cytokines, oxidative stress, high glucose concentration, toll-like receptor agonists and shear stress [32]. High plasma levels have been observed in COVID-19 patients and are associated with disease progression and mortality [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%